Cost and potential for CO₂ emissions reduction in China's petroleum refining sector: A bottom up analysis - Yuan Li; Beixing Wang; Yanli Xie; Lei Zhu (Energy Reports, 2020)
The petroleum refining sector is energy intensive and has been identified as one of the target industries for CO2 emissions control by China's emissions trading scheme. A detailed accounting of the cost of emissions reduction is of great significance for the petroleum refining sector to comply with emission reduction target. In this paper, six categories of CO2 abatement technologies are identified in China's petroleum refining sector, their CO2 emissions reduction cost as well as the potential are estimated using a bottom-up method. Most of the technologies in the sector are cost-effective, which has contributed approximately 76.4% of sectoral total emissions reduction. New equipment technology provides the greatest contribution to emissions reduction, while new materials technology offers the lowest contribution. The implementation of the emissions trading scheme will increase the potential for emissions reduction only if the CO2 price can be higher than 200 CNY/t. Given the amount of emissions reduction that technologies can provide will not exceed 40% of the total emissions; firms must find more diversified ways when facing more stringent emissions control.
Keywords: 330; Abatement technology; Bottom up analysis; CO emissions reduction cost; CO emissions reduction potential; Conserved supply curve; Petroleum refining sector